The epistemology of essential production theory - Mohammad hosein Safaee (مطالعات فقه و حقوق اسلامی, 2023)
In recent years and with the entrance of some branches of contemporary philosophy (such as epistemology) into religious knowledge, the necessity of applying these new grounds in religious knowledge take notice of many more than ever. Although in Principles of Islamic jurisprudence (usul al-fiqh) as one of religious knowledges, justification of knowledge is considered to some extent, but the aforementioned factors aren't examined in detail or its way of justification has radical differences with common epistemologies. In this paper, after posing essential validity of certainty as a realistic belief and the role of this theory in usul al-fiqh, one of most famous (and perhaps most perfect) Usuli’s knowledge theories concerning the method of obtaining justified belief, called “production theory” which is introduced by martyr sadr, will be put forth, consider and criticize. It seems that despite martyr sadr’s attempts for explaining the method of knowledge justification in usul al-fiqh, still in essential validity of certainty, the subjectivist theme of essential production theory and induction problem is bolder than objectivism. On account of that, paying attention to objectivist explanations and applying its entailments in usul al-fiqh become necessary again and the mechanisms of metaphysical realism concerning divine orders must be revised by Usuli theories.